A Rare Case of Leiomyomatosis Peritonealis Disseminata With Endometriosis. (21st September 2018) - Reddy, Amit; Kaur, Jaswinder; Neill, James
Abstract: Introduction: Leiomyomatosis peritonealis disseminata (LPD) is a rare benign disorder characterized as numerous smooth muscle nodules in the peritoneal cavity. LPD is difficult to diagnose by clinical evaluation due to unknown etiology and incidental findings. To date, fewer than 200 cases have been reported and one other case of LPD with endometriosis and ascites has been documented. LPD commonly occurs in reproductive age and rarely is seen in postmenopausal women. We present LPD in a postmenopausal woman with endometriosis. Case Report: A 54-year-old female presented with pain, nausea, vomiting, and weight loss. Physical exam demonstrated a palpable mass arising from the adnexa. CT scan showed a 6.4-cm large multiloculated heterogeneous mass in the right adnexa concerning for ovarian carcinoma, a large 17-cm fibroid uterus, extensive peritoneal carcinomatosis, small volume of ascites, and numerous hypodense metastatic liver lesions. CT-guided biopsy of peritoneal carcinomatosis of omentum revealed spindle cell neoplasm immunophenotypically consistent with leiomyoma and stained positive for desmin, caldesmon, smooth muscle actin, and Ki-67. Microscopy sections of omental mass showed proliferation of poorly circumscribed spindle cells arranged as nodules in short interlacing and haphazard arrangements in omentum. No cytological atypia was seen in spindle cell proliferation. No mitotic activity was identified. Sections of posterior bladder mass showed endometriosis with an adenomyoma pattern of smooth muscle hypertrophy. Immunohistochemistry confirmed strong positive reactivity in spindle cells to desmin and WT1. Findings were consistent with LPD. Discussion: LPD is not considered in the differential diagnosis of multiple peritoneal nodules because of low incidence and unfamiliarity among clinicians. The treatment for this benign condition is conservative because in most cases, malignant transformation is rare and tumors regress. For conclusive diagnosis of LPD, radiological imaging proves challenging; thus, direct sampling is required to exclude any malignancies. LPD is problematic to identify clinically, so diagnosis is dependent on pathological and surgical results; nevertheless, the prognosis is often good.